Selection, de-selection and progression in German football talent promotion - Güllich, A. (European Journal of Sport Science, 2014)
This study explored to which extent the development of German professional football players is based on early talent identification (TID) and long-term nurture in talent promotion (TP) programmes or on their emergence in the course of repeated procedures of player selection and de-selection in these programmes through childhood and youth. The annual turnover of squad members in national junior teams (2001-2013) and youth elite academies was calculated; national U-team members were followed up with regard to nominations through subsequent seasons and to their success level eventually achieved at senior age; and all current Bundesliga players were analysed retrospectively regarding their earlier involvement in TID/TP programmes. Analyses revealed that the mean annual turnover of squad members was 24.5% (youth academies) and 41.0% (national U-teams), respectively. At any age, the probability of persisting in the programme three years later was <50%. Among current Bundesliga players, the age of recruitment into the TID/TP programme was widely evenly distributed across childhood and youth, respectively. Accordingly, the number of (future) Bundesliga players who were involved in TID/TP was built up continuously through all age categories. The observations suggest that the collective of professional players emerged from repeated procedures of selection and de-selection through childhood and youth rather than from early selection and long-term continuous nurture in TID/TP programmes. The findings are discussed with regard to the uncertainty of TID and of interventions applied to the selected players, and they are related to the individualistic and collectivistic approach in TP.